Application of Reflective Journal Integrated with Literacy to Students' Critical Thinking Ability on Ecosystem Material - Nisfia, Laila; Mubarok, Ibnul (Journal of Biology Education, 2024)
This study aims to analyze the effect of applying reflective journals integrated with literacy on students' critical thinking skills on ecosystem material. The type of research is quasi-experimental. The population in the study was class X students of SMA Negeri 2 Demak in the 2023/2024 academic year. The research sample was class X.11 as the experimental class and class X.12 as the control class. The data collection techniques used were non-test, test, questionnaire and observation methods. Based on data analysis, the level of learning implementation by applying reflective journals integrated with literacy is 91.25% in the excellent category. Questionnaire analysis of students' responses to learning showed that 33% of students responded to the questionnaire in the excellent category, 63.9% of students in the good category, and 2.8% of students in the fair category. The effect of applying reflective journaling integrated with literacy on critical thinking skills was measured by pretest and posttest in classes X.11 and X.12, then calculated using the N-Gain test. The N-Gain test results obtained in the experimental class amounted to 32.75% with a moderate category and in the control class amounted to 13.1% with a low category. These results indicate that the increase in critical thinking skills in the experimental class is higher than the control class. The results of the Spearman Rank correlation test showed a Sig. (2-tailed) of 0.001 and the correlation coefficient value of 0.545. Based on these results, it can be concluded that the application of reflective journals integrated with literacy has a significant effect with a moderate category on students' critical thinking skills on ecosystem material.